2021
DOI: 10.1155/2021/5710440
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Protein Product Promotes Oxidative Accentuation in Renal Epithelial Cells via the Soluble (Pro)renin Receptor‐Mediated Intrarenal Renin‐Angiotensin System and Nox4‐H2O2 Signaling

Abstract: Full-length (pro)renin receptor (fPRR), a research hotspot of the renin-angiotensin system (RAS), plays a serious role in kidney injury. However, the relationship between fPRR and advanced oxidation protein product (AOPP) remains largely unexplored. This study was aimed at exploring the effect of fPRR, especially its 28 kDa soluble form called soluble PRR (sPRR), in AOPP-induced oxidative stress in HK-2 cells, a renal proximal tubular epithelial cell line. Incubation of HK-2 cells with 100 μg/ml AOPP resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Based on our previous study, AOPPs-RSA was shown to cause injury to kidney tubular epithelial cells by activating the PRR/Nox4/H 2 O 2 pathway [ 16 ]. As expected, we found that AOPPs-RSA administration also significantly increased urinary and renal cortical H 2 O 2 excretion, and PRO20 treatment antagonized these responses ( p < 0.05) ( Figure 4 D,E).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on our previous study, AOPPs-RSA was shown to cause injury to kidney tubular epithelial cells by activating the PRR/Nox4/H 2 O 2 pathway [ 16 ]. As expected, we found that AOPPs-RSA administration also significantly increased urinary and renal cortical H 2 O 2 excretion, and PRO20 treatment antagonized these responses ( p < 0.05) ( Figure 4 D,E).…”
Section: Resultsmentioning
confidence: 99%
“…The present study aimed to investigate the potential of Nox4 as a therapeutic target for AOPPs-RSA-induced kidney disease by examining its role in the pathogenesis of AOPPs-RSA. In vitro, we observed that AOPPs-HSA upregulated Nox4 expression in human HK-2 cells [ 16 ]. Furthermore, the present study demonstrated that AOPPs-RSA can upregulate NOX4 expression and generate H 2 O 2 in AOPPs-RSA rats, suggesting that AOPPs-RSA/NOX4 are capable of forming a positive feedback loop via H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent studies on sPRR, especially the effect of sPRR activating AT1R, implied that sPRR might also participate in heart disease pathogenesis, which requires further study. Some researchers have suggested that sPRR led to tissue fibrosis via the PI3K-AKT pathway and could also cause oxidative stress via NOX4 in renal proximal tubular cell lines ( 91 , 92 ). It is still not clear whether sPRR has the same effect on the myocardium.…”
Section: The Roles Of Prr and Sprr In Cardiovascular Diseasesmentioning
confidence: 99%